Vitamin D insufficiency is associated with subclinical atherosclerosis in HIV-1-infected patients on combination antiretroviral therapy. Issue 6 (2nd November 2019) - Calza, Leonardo; Borderi, Marco; Granozzi, Bianca; Malosso, Pietro; Pancaldi, Livia; Bon, Isabella; Re, Maria Carla
Abstract : Objectives: Vitamin D insufficiency has been associated with faster progression of atherosclerosis and increased cardiovascular disease risk, but limited data are available in HIV-infected people. So, we examined potential correlation between vitamin D status and atherosclerosis in people living with HIV. Methods: A cross-sectional study was performed including adult HIV-infected patients on stable antiretroviral therapy, aged 40–60 years, and with a recent carotid ultrasonography. Subclinical atherosclerosis was defined as a carotid intima-media thickness (IMT) ≥0.9 mm at any site. Patients with diabetes mellitus or atherosclerotic cardiovascular disease were excluded. Results: On the whole, 188 patients were enrolled: 86.2% were men and the mean age was 49.1 years. The mean CD4 T lymphocyte count was 567 cells/mm 3, 176 (93.6%) had plasma HIV RNA <20 copies/mL, 51.1% were smoker, 29.2% had hypertension, 27.7% metabolic syndrome, and 44.7% LDL cholesterol >150 mg/dL. The mean serum concentration of vitamin D was 35.2 ng/mL, and 84 (44.6%) patients had a vitamin D insufficiency (<30 ng/mL). Subclinical atherosclerosis was reported in 105 (55.8%) and the mean vitamin D concentration was significantly lower among patients with subclinical atherosclerosis than among those without (18.2 vs 41.3 ng/mL, p  < 0.001). Moreover, the multivariate linear regression analysis adjusted by confounding factors showed an independent association between subclinical atherosclerosis and vitamin D insufficiency, age >50 years, smoking, hypertension, metabolic syndrome, higher BMI, higher LDL cholesterol, longer duration of HIV infection, lower nadir CD4 cell count, and longer exposure to boosted protease inhibitors. Conclusion: In our study, vitamin D insufficiency is significantly associated with subclinical atherosclerosis, so its role in HIV-associated cardiovascular disease should be further evaluated as a possible target for intervention.